GANJARAN DAN HUKUMAN DALAM PERSPEKTIF AL-QURAN DAN HADIST - Rodi, Rodi; Charles, Charles (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
The terms of reward and punishment in the Qur'an are called Targhib wa Tarhib. Rewards and punishments aim to stimulate people to always do good. If it is associated with learning, Reward means a gift and punishment means a sanction for violating the rules that have been agreed upon. Rewards and punishments are a method of learning. These two methods are very effective, given to students under certain conditions. Rewards are given to outstanding students but the prizes are not excessive. While the punishment given to students aims to provide a deterrent effect so as not to repeat the same mistake. Punishment should not be in the form of violence but must be educational. Therefore, Rasulullah SAW gave an example by giving a direct warning. This article describes the effectiveness of the reward and punishment method in learning according to the Qur'an. In this study, the authors used library research, namely collecting materials by reading books, articles, magazines and others in the form of literature. This study uses a qualitative descriptive research method. To take verses in their interpretation based on the theme by collecting verses that have the same direction.